HUBUNGAN PENGETAHUAN DAN PERILAKU IBU DENGAN PEMBERIAN MP-ASI PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS SIMPANG TERITIT KABUPATEN BENER MERIAH TAHUN 2023 - Mauliyani; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2024)
ABSTRACTComplementary Foods for Breast Milk are foods that contain nutrients, which are given to babies or children aged over 6-24 months to meet nutritional needs other than breast milk. To find out whether there is a relationship between maternal knowledge and behavior and giving MP-ASI to babies aged 0-6 months in the Simpang Teritit Community Health Center working area. This research uses quantitative research with a cross-sectional approach. The population was 30 mothers with the entire research sample from the total population in the Simpang Teritit Community Health Center Working Area, namely 30 people. by distributing questionnaires. Of the 30 respondents, it showed that there was a relationship between knowledge of the P-Value value of 0.01 (P ≤ 0.05) and behavior of the P-Value value of 0.00 (P ≤ 0.05). There are still mothers who give mp-asi to their babies too early, it is hoped that mothers can know the effects of giving mp-asi to babies 0-6 months. Keywords : Knowledge, Behavior, Complementary Foods for Breast Milk (MP-ASI)